A Review of Solar Assisted Radiant Heating System: Experimentation and Simulation Approach - Acharya, Ananta; Koirala, Robin; Banjankar, Chirag; Khanal, Shuvas; Baral, Bivek (Kathmandu University Journal of Science, Engineering and Technology, 2021)
The rate of energy consumption on the household level for heating and cooling is increasing annually. Due to economic growth and improved living standard, there is a sense of urgency of heating and cooling system for thermal comfort. Considering the thermal comfort, energy consumption, and impact on the environment, researchers and engineers need to focus on innovative heating and cooling solutions. The radiant heating system, which is popular among the Nordic countries, can be a promising future heating solution for Nepali buildings. This paper provides a brief overview of the solar-assisted floor heating system (SAFHS), experimentation, and simulation approach. Three types of paper included for review, the first type- experimental investigation on the floor heating system (FHS), the second type- simulation using ANSYS, and the third type- numerical analysis using TRNSYS. Out of forty-two papers selected for the study. The maximum papers used an experimental approach (11 articles) or TRNSYS (13 documents) to conduct temperature measurement, performance analysis, economic analysis, and estimate the solar fraction. ANSYS Fluent for the simulation of heat flux out of the system (9 papers), temperature field (11 articles), and the thermal comfort analysis (9 documents). 13 articles performed experiments combined with simulation under a standard protocol to validate the model. Both tools provide accurate results with an error below 10 %. The experimental study should be under the standard protocol, while TRNSYS should study the energy performance analysis, economic analysis, etc. The ANSYS Fluent simulates the thermal performance, temperature field, velocity field and conducts thermal comfort analysis. Based on the review, future research should be on taking combined advantages using the coupled-simulation approach.